Resilience and Self-Efficacy as Predictors of Teacher Motivation in Indonesia - Syarifuddin Syarifuddin; Muhammad Fahreza; Amiruddin Hamzah; Elpisah Elpisah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The low motivation of some teachers in Indonesia to carry out their professional duties affects the quality of the learning process and outcomes. This condition is thought to be related to teachers' resilience and self-efficacy, which play a crucial role in determining their perseverance, confidence, and enthusiasm in facing job challenges. This study aims to examine the role of resilience and self-efficacy in predicting teachers' teaching motivation in the Indonesian educational context. This study used a quantitative survey method. Data were collected via an online questionnaire comprising 34 valid and reliable items. A total of 217 teachers from various educational levels voluntarily participated. Multiple regression analysis using SPSS revealed that the model explained 28.7% of the variance in teaching motivation. The results showed that self-efficacy had a significant positive effect, while resilience showed a significant negative effect. These findings emphasize that self-efficacy directly increases teacher motivation, whereas resilience primarily serves as a coping mechanism in the face of systemic pressures. Theoretically, this study enriches educational research by integrating major theories that explain the determinants of teacher motivation. In practice, the research results emphasize the importance of increasing self-efficacy and institutional support so that teacher resilience not only maintains steadfastness but also fosters sustainable teaching motivation.